An Analysis of Direct And Indirect Apology in The Daredevil First Season (2015) Series - Hagi Alwirido; Oktiva Herry Candra (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
This research is about the analysis of the speech act of apology strategy. The researcher analyzes theapology strategies phenomenon in the Daredevil First Season (2015) series. The study aims toreveal the direct and indirect apologies and the social functions of the apologies produced by thecharacters in the series. The research method of this study adheres to descriptive qualitative, withnon-participatoryobservationasthemethodofcollectingdata.Then,thecollecteddataisanalyzedusing [8] and [6]. The researcher discovers that both direct and indirect apologies are used by thecharacters in this series with direct apologies as the most frequently used apologies strategy.There are also 5 social functions of the apology expressed by the characters in the series, namelyshowing good manners, showing contrition, asking to be forgiven, getting off the hook, andassuaging the addressee’swrath.